An analysis of culture and gender in resource access, utilisation and management in community and forest reserves in Ntchisi District, Malawi - Chirwa, Paxie W. (University of Pretoria, 2020)
Dissertation (MSc (Forest Management and Environment))--University of Pretoria, 2020.